Family and Community Medicine and Challenges in comprehensive care for migrant populations: A look at refugees in the context of vulnerable populations (Research, Society and Development, 2024)
The study of neglected populations is directly associated with opportunities and social support in territories, enabling them to be welcomed and maintain their lives even when immersed in processes of oppression, violence, and human rights violations. In Brazil, the guarantee of health as a human right, and not as a commodity, makes this country one of the possibilities for attracting populations needing refuge, with a growth in demand aligned with the change in global migration flows and processes. However, despite the qualities that attract immigrants from various regions to Brazil, the country still lacks well-defined policies and planning for training teams, ensuring access, active search for complex cases, and understanding cultural issues that should be valued for effective health care. These skills are inherent to the training of family and community medicine, aimed at working in the territory using the person-centered clinical method to understand manifestations of health and disease in the context of physical, mental, and social multimorbidity, aggravated by the situation of oppression, violence and stigma increased against refugee populations, victims of marginalization and human rights violations in the most diverse countries in the world. Through an analysis of the literature, this research aims to reflect on the relationships of social determinants in the vision of refugee and migrant health, showing a vision of opportunities for welcoming these patients in an intersectoral vision of public health.